2010
DOI: 10.1016/j.juro.2010.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Urological Malpractice: Analysis of Indemnity and Claim Data From 1985 to 2007

Abstract: Urology tends to be at or below average compared to other medical specialties in regard to total claims, total monies paid and average monies paid during the last 23 years. From 1997 to 2007 the average indemnity paid increased by 23%. Improper performance, diagnostic errors and failure to monitor cases resulted in the most lawsuits. In those groups malignancy of the prostate, testis and kidney appeared consistently. Continued analysis and education on medical litigation in urology can aid in increased awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
0
13
1
6
Order By: Relevance
“…This is a group of companies, which between them provide insurance protection to >60% of private practitioners in the USA, and write ≈46% of the total industry premium. The PIAA’s summary data of claims for urology from 1985–2007 showed a total of 5 577 claims with $285 million paid during the 22‐year study period[5]. The average paid per claim was $174 245 which, using exchange rates at the time of writing, is more than double that in the present study.…”
Section: Discussioncontrasting
confidence: 40%
“…This is a group of companies, which between them provide insurance protection to >60% of private practitioners in the USA, and write ≈46% of the total industry premium. The PIAA’s summary data of claims for urology from 1985–2007 showed a total of 5 577 claims with $285 million paid during the 22‐year study period[5]. The average paid per claim was $174 245 which, using exchange rates at the time of writing, is more than double that in the present study.…”
Section: Discussioncontrasting
confidence: 40%
“…11-13 A recent American Medical Association (AMA) survey of physicians showed that 5% of respondents had faced a malpractice claim during the previous year. 14 Studies estimating specialty-specific malpractice risk from actual claims are much less recent, 15,16 including a Florida study from 1975 through 1980 showing that 15% of medical specialists, 34% of obstetricians and anesthesiologists, and 48% of surgical specialists faced at least one claim that resulted in an associated defense cost or payment to a claimant (an indemnity payment) during the 6-year study period.…”
mentioning
confidence: 99%
“…Each of these earlier studies has limitations, including the use of older data 15-17 with limited geographic coverage, 17 reliance on self-reports with limited sample size and low response rates, 14 limited information on physician specialty, 13,14 and a lack of information on the size of payments. 14 Although the National Practitioner Data Bank includes most cases in the United States in which a plaintiff was paid on behalf of a licensed health care provider, 18 it does not report the specialties of physicians and does not record information on cases that do not result in a payment.…”
mentioning
confidence: 99%
“…surgical specialists faced at least one claim that resulted in an associated defense cost or payment to a claimant (an indemnity payment) during the 6-year study period. 17 Each of these earlier studies has limitations, including the use of older data [15][16][17] with limited geographic coverage, 17 reliance on self-reports with limited sample size and low response rates, 14 limited information on physician specialty, 13,14 and a lack of information on the size of payments. 14 Although the National Practitioner Data Bank includes most cases in the United States in which a plaintiff was paid on behalf of a licensed health care provider, 18 it does not report the specialties of physicians and does not record information on cases that do not result in a payment.…”
mentioning
confidence: 99%